CONSUMER COMPLAINT BEHAVIOUR IN INDONESIA: ROLE OF KNOWLEDGE AND SELF-CONFIDENCE - Azizah, Sheila Nur; Simanjuntak, Megawati; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2022)
Complaint behavior is a person's response to dissatisfaction with the goods or services used. Complaints are feedback from customers that tend to be negative towards the company. Self-confidence can be interpreted as one aspect of personality in the form of belief in one’s abilities so that others do not influence him, can act according to his will, are happy, optimistic, relatively tolerant, and responsible. This study generally aims to analyze the effect of knowledge and self-confidence on complaints in Indonesia. The study used a cross-sectional study design. The samples were married or employee consumers aged between 17 to 60 years determined by multi-stage random sampling. The number of samples in this study was 2.100 respondents. This study used descriptive analysis, independent t-test, and SEM using Linear Structural Relationship (LISREL) 8.72. The findings of this study indicate that the knowledge and respondents' complaint behavior are relatively low, whereas self-confidence was in the moderate category. Knowledge had a significant effect on complaint behavior but insignificant on self-confidence. Other results also indicate that self-confidence had no significant effect on complaint behavior.